PARADIGMA PENELITIAN TAFSIR AL-QURâ€™AN DI INDONESIA (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Studies on the works of Quranic exegesis (kitÄb al-tafsÄ«r) as developed in literatures have been so far orientedÂ to unveil technical aspects, methods, and characteristics of the works. Works by al-FarmÄwÄ«, Yunan Yusuf,Nasrudin Baidan, for example, share a common tendency in their approaches. Despite of the importance of suchÂ works, the current studies on the works of tafsÄ«r are still lack of a comprehensive methodology that enablesÂ us to figure out epistimelogical and socio-cultural landscapes of a certain work on tafsir. Using a criticalÂ discourse analysis and epistemÃ© of journalistic writing model as the basis, this paper attempts to develop a newÂ paradigmatic construction by which any interests, discourses, ideologies and oppositional spirits against sociopoliticalÂ facts in tafsÄ«r works are revealed.Keywords: Tafsir, Analisis Wacana Kritis, Teks Kultural